2011
DOI: 10.1534/genetics.111.127696
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdoviruses in Two Species of Drosophila: Vertical Transmission and a Recent Sweep

Abstract: Insects are host to a diverse range of vertically transmitted micro-organisms, but while their bacterial symbionts are well-studied, little is known about their vertically transmitted viruses. We have found that two sigma viruses (Rhabdoviridae) recently discovered in Drosophila affinis and Drosophila obscura are both vertically transmitted. As is the case for the sigma virus of Drosophila melanogaster, we find that both males and females can transmit these viruses to their offspring. Males transmit lower vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(89 citation statements)
references
References 55 publications
4
85
0
Order By: Relevance
“…Over 200 rhabdoviruses have been identified (31), and a majority of the plant rhabdoviruses and some vertebrate rhabdoviruses use an insect vector for transmission. However, only a few rhabdoviruses have been directly isolated from insects or insect cell lines; these belong to the order Diptera (such as sigma viruses in Drosophila and Muscina flies [26,32,33] and the Culex tritaeniorhynchus rhabdovirus [CTRV] in Culex mosquitoes [34]) and to the order Hemiptera (such as Taastrup virus in the leafhopper [25]). We report here the discovery of a novel rhabdovirus in the Spodoptera frugiperda Sf9 cell line, which is the first rhabdovirus found in the order Lepidoptera.…”
Section: Discussionmentioning
confidence: 99%
“…Over 200 rhabdoviruses have been identified (31), and a majority of the plant rhabdoviruses and some vertebrate rhabdoviruses use an insect vector for transmission. However, only a few rhabdoviruses have been directly isolated from insects or insect cell lines; these belong to the order Diptera (such as sigma viruses in Drosophila and Muscina flies [26,32,33] and the Culex tritaeniorhynchus rhabdovirus [CTRV] in Culex mosquitoes [34]) and to the order Hemiptera (such as Taastrup virus in the leafhopper [25]). We report here the discovery of a novel rhabdovirus in the Spodoptera frugiperda Sf9 cell line, which is the first rhabdovirus found in the order Lepidoptera.…”
Section: Discussionmentioning
confidence: 99%
“…through both eggs and sperm) [30,31]. Additionally, the trait of being paralysed by CO 2 that has been reported in Drosophila athabasca and C. quinquefasciatus is transmitted vertically in the biparental manner that is characteristic of sigma viruses [34,46].…”
Section: Biparental Transmission Of Sigma Virusesmentioning
confidence: 99%
“…The speed with which sigma viruses can spread is illustrated by recent work on DObsSV in populations of D. obscura [31]. By sequencing viral isolates collected from across the UK, it was found that the viral population shows clear evidence of a recent expansion, with low genetic diversity and an excess of rare polymorphisms.…”
Section: Population Dynamics and The Cost Of Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hallmark in the life cycle of insect-specific sigmaviruses is the exclusively vertical transmission through eggs and sperm (Longdon et al, 2011). Currently, no data are available to decide to what extent horizontal or vertical transmission contribute to the maintenance of MERDV in nature.…”
Section: Discovery Of a Novel Rhabdovirus In Mexican Mosquitoesmentioning
confidence: 99%